IMPLEMENTING READING TO LEARN PEDAGOGY IN CLIL LESSONS: THE CASE OF AN INDONESIAN SECONDARY SCHOOL - Komarawan, Yulizar (SEAQIL Journal of Language Education, 2024)
In recent years, content and language integrated learning (CLIL) has gained popularity among educators across the world, including in Indonesia. In classroom practice, various procedures have been applied to conduct CLIL lessons. One of them is the Reading to Learn (R2L) pedagogy developed in the Systemic Functional Linguistic tradition. This current study illustrates how R2L pedagogy was employed in an Indonesian CLIL biology lesson. To achieve the goal, the study used a qualitative case study. The data were obtained from video recordings of classes during the implementation at a private school in Bandung Barat, Indonesia. At the time of the teaching, the R2L pedagogy was applied in the classroom to embed English literacy in biology lessons for senior high school students. From the pedagogic register analysis of the selected lesson, it was revealed that the lesson consisted of three carefully planned lesson stages. First, preparing for reading immersed students in daily life and helped them acquire basic knowledge by using images or diagrams. Subsequently, detailed reading was carefully prepared to connect the activated knowledge with human digestive systems (disciplinary knowledge). Here, the students read the given text to identify technical processes in the digestive system in each organ, jotted them down in the form of notes, and elaborated on the terms. At the last stage, the observed teacher incorporated the scientific terms into new writings during a joint construction activity. R2L pedagogy, as described here, supports educators in delivering interactive CLIL lessons effectively and enables educators to promote embedded literacy in classrooms.